Investigating the effect of the educational intervention based on the Health Belief Model on the knowledge and beliefs of Yemeni teachers in the use of breast cancer screening: a randomized controlled trial study - Noman, Sarah; Elarusy, Nadya Mohamed Elfeturi; Rahman, Hejar Abdul; Ismail, Suriani; Azzani, Meram; Taresh, Sahar Mohammed; Aljaberi, Musheer A. (Springer Nature, 2024)
Background: Breast cancer (BC) is the most prevalent cancer among women. Teachers play a crucial role in promoting healthy behaviors, including breast cancer screening (BCS). This study aimed to assess the impact of an Health Belief Model (HBM)-based educational intervention on BCS uptake, knowledge, and beliefs among female Yemeni teachers in Klang Valley, Malaysia. Methods: A cluster-randomized controlled trial was conducted with 180 participants from 12 schools, randomly assigned to intervention or control groups. The intervention group participated in a 90-minute educational session, with follow-up assessments at baseline, and at 1, 3, and 6 months’ post-intervention, using validated Arabic questionnaires. Data analysis was performed using SPSS version 22.0, with Generalized Estimating Equations (GEE) applied to assess differences within and between groups over time. Statistical significance was set at P < 0.05. Results: At baseline, there were no significant differences between groups. Post-intervention, the intervention group showed significantly higher rates of breast self-examination (BSE) and clinical breast examination (CBE) compared to the control group, with adjusted odds ratios (AOR) of 17.51 (CI: 8.22–37.29) for BSE and 2.75 (CI: 1.42–5.32) for CBE. Over six months, BSE performance in the intervention group increased, with AORs improving from 11.01 (CI: 5.05–24.04) to 18.55 (CI: 8.83–38.99). Similarly, CBE uptake rose from 1.60 (CI: 1.02–2.52) to 2.27 (CI: 1.44–3.58). Secondary outcomes revealed significant gains in knowledge and beliefs in the intervention group, including increased confidence in performing BSE and reduced perceived barriers. Conclusions: The HBM-based educational intervention effectively enhanced BCS uptake, improved knowledge, and decreased barriers to BCS among Yemeni teachers in Malaysia, highlighting the potential of targeted educational programs to promote cancer screening behaviors in underserved populations. Clinical trial registration: Retrospectively registered, ANZCTR (ACTRN12618000173291). Registered on February 02, 2018.